Statistical Assessment of the State and Quality of Nutrition of the Population of the Republic of Mordovia - M. V. Bikeeva; E. A. Sysoeva; I. V. Paramonova (Статистика и экономика)
Purpose of the study. The article presents the results of a statistical analysis of the nutritional characteristics of the population of the Republic of Mordovia to assess their eating behavior in accordance with the principles of healthy nutrition.The results of the study showed inconsistency with rational standards of consumption of basic food products by the population of the republic. The most pronounced deficit in the diet of the population of the republic is observed in the consumption of vegetables and melons, milk and dairy products and vegetable oil. Significant excess of the recommended norm is typical for the consumption of sugar, bread products, potatoes, meat, meat products and eggs. A reduction in the food energy value of the daily diet was revealed to 2600 kcal versus 3126 kcal according to rational consumption standards.Materials and methods. As a methodological basis for the study, an aggregation method was used, which makes it possible to calculate indexes of the benefits of consumption of basic food products by the population of the Volga Federal District regions: advance, parity and lag from recommended rational consumption standards. The calculation of the integral assessment of the nutrition quality of the population was carried out without taking into account the weighting coefficients of the main food groups.The information base of the study is data from the Federal State Statistics Service. The results of the study confirm the existence of differentiation in food consumption and its quality in the regions of the Volga Federal District. Not a single region has been identified with parity in terms of recommended rational nutritional standards. In two regions (Udmurt and Chuvash Republics), there is an approximation to rational consumption standards. In four regions of the Volga Federal District (Perm Krai, Penza, Saratov and Ulyanovsk regions) consumption lags behind the recommended rational norms. In other regions, there is an excess of rational consumption standards for most food products. This group of regions includes the republics of Bashkortostan, Mari El, Mordovia, Tatarstan, Kirov, Nizhny Novgorod, Orenburg and Samara regions. For the Republic of Mordovia, the value of the integral assessment was 1,052.Conclusions. The need to continue activities to develop healthy lifestyle priorities among the population through a culture of nutrition, as laid down in the Federal Project “Strengthening Public Health” was noted.